Islamic Value-Based Quality Management: The Challenge of Spiritual Integration in Modern Education Systems - Fadhlillah Fadhlillah; Jibril Ayuba (Yayasan Avicenna, 2024)
The application of quality management based on Islamic values has the potential to shape students’ holistic character by integrating cognitive, affective, and spiritual dimensions. However, the integration of modern management systems with spiritual values often remains conceptually fragmented and lacks a structured implementation framework. This study aims to explore the challenges of integrating spiritual values into modern educational management systems within Islamic educational institutions. Using a qualitative approach with a case study design, data were collected through participant observation, in-depth interviews with school leaders and teachers, and documentation analysis. The findings of the study reveal several key challenges in the integration process. First, there is a conceptual gap between managerial efficiency emphasized in modern systems and the moral-spiritual orientation upheld in Islamic values. Second, institutional resistance emerges due to the lack of understanding and capacity of school leaders in harmonizing both paradigms. Third, the absence of standardized indicators for measuring spiritual dimensions makes the integration process ambiguous and inconsistent. Fourth, external pressures such as accreditation demands and bureaucratic expectations often prioritize measurable outputs over spiritual growth. Lastly, there is limited professional development for educators in implementing spiritually grounded quality management. These challenges suggest the need for a comprehensive framework that aligns modern quality management principles with Islamic educational philosophy, supported by policy, training, and contextual adaptation within the institution.